Analysis of Factors Related to Stigma of Health Worker and Medical Personnel Towards Hepatitis B at RSUDZA Banda Aceh - Bakar, Azzaki Abu; Yusuf, Fauzi; Renaldi, Teuku; Salawati, Liza; Mahesa, Pocut Diva; Edward, Meutia Nailan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Hepatitis B is one of the infection disease that attacks liver and is often accompanied by stigma including among health worker and medical personnel. This research aiming for analyze related factors with the stigma of health worker and medical personnel towards Hepatitis B at RSUDZA Banda Aceh. Methods: This study was an observational analytics with design cross sectional. Data collection was conducted on November 19-29 at RSUDZA. The sample consisted of from 452 health workers and medical personnel at RSUDZA Banda Aceh which was selected use method accidental sampling. Results: Research results shows 49.6% health worker and medical personnel at RSUDZA Banda Aceh has high (i.e.: negative or discriminatory) stigma towards Hepatitis B. The results of data analysis using the Chi-square test with 95% CI and α 0.05 showed level of knowledge, profession and services have significant relationship with stigma towards hepatitis B, while age, gender, length of service, and training did not show a significant relationship.Conclusion: It can be concluded that there is a relationship between the level of knowledge, profession, and service with the stigma of health workers and medical personnel towards Hepatitis B. And there is no relationship between factors of age, gender, length of service and training with stigma towards Hepatitis B